5z-9z=-7z-7-z

Simple and best practice solution for 5z-9z=-7z-7-z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z-9z=-7z-7-z equation:


Simplifying
5z + -9z = -7z + -7 + -1z

Combine like terms: 5z + -9z = -4z
-4z = -7z + -7 + -1z

Reorder the terms:
-4z = -7 + -7z + -1z

Combine like terms: -7z + -1z = -8z
-4z = -7 + -8z

Solving
-4z = -7 + -8z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '8z' to each side of the equation.
-4z + 8z = -7 + -8z + 8z

Combine like terms: -4z + 8z = 4z
4z = -7 + -8z + 8z

Combine like terms: -8z + 8z = 0
4z = -7 + 0
4z = -7

Divide each side by '4'.
z = -1.75

Simplifying
z = -1.75

See similar equations:

| 40=x(x+3) | | 2x+x/2+x+20=580 | | (5w+1)(2-w)=0 | | (1.5*b)*b=0 | | 1.5b*b=0 | | X*2=-9x-8 | | 3x-5-2x=5-12 | | 0.5(4x-2)= | | (5x-90)=2x+30 | | C-6c=0 | | (11r+6)(5r-4)=0 | | Y=0.6(100)+b | | 6n^2/2 | | x+13=5x | | 5(x)=5(2x-3) | | R=b^2+1 | | (5x)2=15x-45 | | 3c-1=c | | 3x-5-x=2x-3 | | 3ysquared= | | 3(2x+1)-2(3-2)=13 | | 15x-45/2=5x | | 1/3x3/8 | | (7a)x(2b)=0 | | 15/105 | | 9z+4-5z-5= | | -6(r-7)=-54 | | 8+9a=7 | | 4x+3+2y=11 | | 7x-4.23=0.2+2.57 | | 7x-4.23=0.2 | | -8(n-2)-2=-21-3n |

Equations solver categories